SCREEN TIME, EFFECTS ON COGNITIVE, PSYCHOLOGICAL AND PHYSICAL DEVELOPMENT OF CHILDREN - Jalil, Jawad; Bashir, Faisal (Pakistan Armed Forces Medical Journal, 2021)
The social and cultural milieu of the societies all over the world are in a flux and have already seen a momentous change during last few decades. Though the process of change has been a permanent feature of the human evolution since the beginning of human society but the rate of change has leapfrogged at dizzying speed in last few decades. This has revolutionized the living patterns all over the world and the child rearing practices are no exception to this. The dilution of large joint families, lesser number of children, more involvement of mothers at work place and small family size are few of the factors contributing to this change. The advent of TV, internet and mobile has added another dimension to this. These screens have changed the human behavior and the infants and children are no exception. These screens with their addictive content provide care givers the ideal tool to engage children while they are busy either in their work or entertainment. But this behavior has deleterious effect on the child behavior and development.